2000
DOI: 10.1007/bf03343684
|View full text |Cite
|
Sign up to set email alerts
|

GH/IGF-I axis in Prader-Willi syndrome: Evaluation of IGF-I levels and of the somatotroph responsiveness to various provocative stimuli

Abstract: Basal IGF-I levels and the GH response to at least two among provocative stimuli such as clonidine (CLO, Catapresan, 150 mcg/m2 p.o.), GHRH (1 mcg/kg i.v.)+arginine (ARG, 0.5 g/kg i.v. infusion during 30 min) and GHRH+pyridostigmine (PD, Mestinon cpr 60 mg p.o.) have been evaluated in 43 children with Prader-Willi syndrome (PWS, 17 males and 26 females, age 3-22 yr, 7 normal weight and 36 obese PWS), in 25 normal short children (NC, 17 males and 8 females, 7.7-18.5 yr) and in 24 children with simple obesity (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 32 publications
2
32
0
4
Order By: Relevance
“…22,28 In addition, previous reports support the hypothesis of an age-dependent derangement of the hypothalamus-pituitary axis occurring in PWS subjects, also regarding GH secretion. In fact, there is evidence of GH insufficiency after reaching final height, although study findings differ largely on the prevalence of this clinical feature in the adult.…”
supporting
confidence: 53%
“…22,28 In addition, previous reports support the hypothesis of an age-dependent derangement of the hypothalamus-pituitary axis occurring in PWS subjects, also regarding GH secretion. In fact, there is evidence of GH insufficiency after reaching final height, although study findings differ largely on the prevalence of this clinical feature in the adult.…”
supporting
confidence: 53%
“…Many studies found that a large percentage of PWS patients had a blunted GH response to standard provocative tests [6,7,8,9,10]. Nevertheless, the majority of these subjects are overweight or obese, a condition which is itself known to reduce the response of GH secretion to pharmacological stimulation tests [11].…”
Section: Introductionmentioning
confidence: 99%
“…Considerando o valor de corte de 5 ng/ml, três pacientes foram não responsivos. Vários autores descrevem a secreção diminuída de GH na SPW como uma irregularidade neurossecretória (16,27).…”
Section: Discussionunclassified